Pistacia lentiscus Oleoresin: Virtual Screening and Identification of Masticadienonic and Isomasticadienonic Acids as Inhibitors of 11β-Hydroxysteroid Dehydrogenase 1 - Vuorinen, Anna; Seibert, Julia; Papageorgiou, Vassilios P.; Rollinger, Judith M.; Odermatt, Alex; Schuster, Daniela; Assimopoulou, Andreana N. (Planta Medica, 2015)
In traditional medicine, the oleoresinous gum of Pistacia lentiscus var. chia, so-called mastic gum, has been used to treat multiple conditions such as coughs, sore throats, eczema, dyslipidemia, and diabetes. Mastic gum is rich in triterpenes, which have been postulated to exert antidiabetic effects and improve lipid metabolism. In fact, there is evidence of oleanonic acid, a constituent of mastic gum, acting as a peroxisome proliferator-activated receptor γ agonist, and mastic gum being antidiabetic in mice in vivo. Despite these findings, the exact antidiabetic mechanism of mastic gum remains unknown. Glucocorticoids play a key role in regulating glucose and fatty acid metabolism, and inhibition of 11β-hydroxysteroid dehydrogenase 1 that converts inactive cortisone to active cortisol has been proposed as a promising approach to combat metabolic disturbances including diabetes. In this study, a pharmacophore-based virtual screening was applied to filter a natural product database for possible 11β-hydroxysteroid dehydrogenase 1 inhibitors. The hit list analysis was especially focused on the triterpenoids present in Pistacia species. Multiple triterpenoids, such as masticadienonic acid and isomasticadienonic acid, main constituents of mastic gum, were identified. Indeed, masticadienonic acid and isomasticadienonic acid selectively inhibited 11β-hydroxysteroid dehydrogenase 1 over 11β-hydroxysteroid dehydrogenase 2 at low micromolar concentrations. These findings suggest that inhibition of 11β-hydroxysteroid dehydrogenase 1 contributes to the antidiabetic activity of mastic gum.
Keywords: Pistacia lentiscus; Anacardiaceae; 11β-hydroxysteroid dehydrogenase; virtual screening; antidiabetic; diabetes